Whey pretreatment ameliorates gastric and hepatic oxidative damage in ethanol-induced gastric ulcer via a neutrophil-dependent mechanism - (:unkn) unknown (My University, 2005)
Objective: Whey is a dietary protein supplement with antioxidant effects. In this study, the protective effects of whey protein against ethanol-induced oxidative gastric injury and associated hepatic injury are evaluated. Methods: Formation of reactive oxygen species in the gastric tissue was monitored, using chemiluminescence technique. Hepatic and gastric tissues were analyzed histologically, while malondialdehyde levels and myeloperoxidase activity of the gastric and hepatic tissues were measured to determine the degree of lipid peroxidation and tissue neutrophil infiltration, respectively. Results: Whey treatment demonstrated protective effects against ethanol-induced gastric and hepatic injury, by inhibiting neutrophil infiltration and generation of cytotoxic free radicals. Conclusion: A nutritional approach with a whey-based product might offer an attractive new choice to support the treatment of gastric lesions.
Keywords: Ethanol; Gastric and hepatic oxidative damage; Whey proteins